Improving Student Learning Outcomes in Economics Subjects Through Project Based Learning Models - Feri Justinus Sitanggang; Caska Caska; Hendripides Hendripides (CV. Rayyan Dwi Bharata, 2024)
This research aims to determine the influence of the Project Based Learning Model on Student Learning Outcomes in Class XI Economics Subjects at SMAN 1 Pekanbaru. The type of research used in this research is descriptive quantitative with an experimental approach. The research subjects used in this research were class XI.5, totaling 36 students. The results of the research that has been carried out show that the project-based learning model influences students' cognitive learning outcomes in class XI economics subjects at SMAN 1 Pekanbaru. This can be seen from the post-test data showing that an average score of 93.88 was obtained. Based on this research, it can be concluded that there is an influence of the project-based learning model on student learning outcomes in class XI economics subjects at SMAN 1 Pekanbaru. Based on the results of hypothesis testing using the paired sample t-test, the student learning outcome value was 0.0000.05.